Widespread clone of Burkholderia cenocepacia in cystic fibrosis patients in the Czech Republic - Drevinek, Pavel; Vosahlikova, Sarka; Cinek, Ondrej; Vavrova, Vera; Bartosova, Jana; Pohunek, Petr; Mahenthiralingam, Eshwar (Journal of medical microbiology, 2005)
The morbidity and mortality rates in patients with cystic fibrosis (CF) are significantly affected by infections with Burkholderia cepacia complex. In a Czech CF Centre, the prevalence of the infection reached up to 30 %, with the majority of patients found to be infected with Burkholderia cenocepacia (formerly genomovar III of the Burkholderia cepacia complex). Since B. cenocepacia is associated with patient-to-patient transmission and epidemic outbreaks among CF patients, this study sought to examine the epidemiological relatedness between the Czech isolates belonging to the genomovar-homogeneous group. Eighty-three clinical isolates recovered from 67 CF patients were analysed using a random amplified polymorphic DNA (RAPD) assay and macrorestriction typing (SpeI and XbaI) followed by PFGE. A single predominant banding pattern shared by multiple isolates was detected, although SpeI-generated PFGE results yielded a higher rate of inter-pattern variability in comparison to the more uniform RAPD and XbaI-generated PFGE results for this clone. Both typing systems also showed that only three out of 67 patients harboured strains distinct from the major strain type. The dominant clone was characterized by PCR positivity for the B. cepacia epidemic strain marker, PCR negativity for the cable pilin subunit gene and close genetic relatedness to the epidemic strain of RAPD 01 type previously identified in Canada.
Keywords: Random Amplified Polymorphic DNA Technique; technika náhodné amplifikace polymorfní DNA; polymerázová řetězová reakce; Male; Burkholderia Infections; infekce bakteriemi rodu Burkholderia; Genotype; Adolescent; Electrophoresis, Gel, Pulsed-Field; Česká republika; Child; pulzní gelová elektroforéza; Burkholderia cepacia complex; Cystic Fibrosis; dítě; DNA fingerprinting; prevalence; Adult; DNA Fingerprinting; dospělí; Burkholderia cepacia komplex; mužské pohlaví; mladiství; Czech Republic; lidé; cystická fibróza; ženské pohlaví; Humans; epidemický výskyt choroby; Prevalence; genotyp; Polymerase Chain Reaction; Disease Outbreaks; Female